Environmentally appropriate vector control is facilitated by standard metrics for simulation-based evaluation - Vásquez, Váleri N.; Reddy, Michael R.; Marshall, John M. (Frontiers in Tropical Diseases, 2022)
As anthropogenic factors contribute to the introduction and expansion of new and established vector species, the geographic incidence of mosquito-borne disease is shifting. Computer simulations, informed by field data where possible, facilitate the cost-effective evaluation of available public health interventions and are a powerful tool for informing appropriate policy action. However, a variety of measurements are used in such assessments; this can complicate direct comparisons across both vector control technologies and the models used to simulate them. The expansion of biocontrol to include genetically engineered organisms is now prompting additional metrics with no analogy to traditional measurement approaches. We propose Standard Entomological Metrics (SEMs) to facilitate the model-based appraisal of both existing and novel intervention tools and define two examples: Suppression Efficacy Score and Time to Reduction Target. We formulate twelve synthetic case studies featuring two vector control technologies over three years of observed daily temperature in Cairns, Australia. After calculating Suppression Efficacy Score and Time to Reduction Target results, we apply these example outcomes to a discussion of health policy decision-making using SEMs. We submit that SEMs such as Suppression Efficacy Score and Time to Reduction Target facilitate the wholistic and environmentally appropriate simulation-based evaluation of intervention programs and invite the community to further discussion on this topic.